1984
DOI: 10.1111/j.1095-8312.1984.tb01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric studies in inbred and hybrid house mice. Heterosis, homeostasis and heritability of size and shape

Abstract: One size (SIZE) and four shape measures (SHAPE ]-SHAPE 4) were derived from a multiple group principal components analysis of 15 osteometric variables in inbred and hybrid house mice. In both sexes, SIZE and two of the four SHAPE variables showed positive heterosis, the other two SHAPE variables exhibiting negative heterosis. SIZE showed a greater magnitude of heterosis (average of about 2.3 standard deviations) than all SHAPE characters except SHAPE 2, a skull length/width contrast. Inbreds were more variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The genetic bases of DS and canalization are for the most part unknown even though an important number of studies have focused on this subject in the last few decades, for example, Leamy & Thorpe (1984), Leamy (1993), Graham (1992) and Clarke (1993b) for DS and Wagner et al (1997) and Eshel & Matessi (1998) for canalization. Except in the case of Lucila cuprina studies, which have stressed the role of a modi¢er gene in DS regulation (e.g.…”
Section: (C) Genetic Bases and Selective Constraintsmentioning
confidence: 99%
“…The genetic bases of DS and canalization are for the most part unknown even though an important number of studies have focused on this subject in the last few decades, for example, Leamy & Thorpe (1984), Leamy (1993), Graham (1992) and Clarke (1993b) for DS and Wagner et al (1997) and Eshel & Matessi (1998) for canalization. Except in the case of Lucila cuprina studies, which have stressed the role of a modi¢er gene in DS regulation (e.g.…”
Section: (C) Genetic Bases and Selective Constraintsmentioning
confidence: 99%
“…In quantitative genetic studies, "size free" shape measures are often constructed using ratios, which have considerable statistical (Atchley et aI., 1976) and interpretative (Bookstein et aI., 1985;Strauss, 1985) problems that detract from their usefulness. However, there seems to be no relationship between relative variability and heritability among mensural traits in either the polychaete Pi/eolaria pseudomilitaris (Beckwitt, 1981) or the amphipod Gammarus minus (Fong, 1988), nor among a series of metric characters (Atchley et a!., 1981) and multivariate size and shape factors (Leamy and Thorpe, 1984) in strains of rats and mice. Even if they exist, such correlations are likely to be age dependent (Atchley and Rutledge, 1980).…”
Section: Discussionmentioning
confidence: 94%
“…The evidence for this is equivocal. Leamy and Thorpe (1984), for example, found greater additive genetic variation associated with size than with shape in osteometric traits in inbred and hybrid house mice. On the other hand, Atchley et al (1981), found nearly uniform heritability of (varimax) rotated principal axes of morphometric traits in the rat.…”
Section: Discussionmentioning
confidence: 99%